(untitled) (Journal of Mathematical Study, 2021)
In this paper, a generalization of q-Gamma operators based on the concept of q-integer is introduced. We investigate the moments and central moments of the operators by computation, obtain a local approximation theorem and get the pointwise convergence rate theorem and also obtain a weighted approximation theorem. Finally, a Voronovskaya type asymptotic formula was given.